Whole Lung Lavage in Autoimmune Pulmonary Alveolar Proteinosis: Unique Challenges in a Resource‐Limited Setting - Ashesh Dhungana; Buddhi Sagar Lamichhane; Prajowl Shrestha; Deepa Kumari Shrestha; Ritamvara Oli; Shreya Dhungana; Pratibha Bista (Clinical Case Reports)
ABSTRACT Autoimmune pulmonary alveolar proteinosis (PAP) is characterized by antibodies to granulocyte–macrophage colony‐stimulating factor (GM‐CSF), alveolar macrophage dysfunction, and surfactant accumulation. Whole lung lavage (WLL) is the treatment of choice in patients with PAP and severe hypoxemia. In resource‐limited settings, WLL can be performed in the intubated, anesthetized patient who is being one lung ventilated using a Y‐type bladder irrigation catheter for saline instillation and drainage.